Inhalation of Fine Particulate Matter Impairs Endothelial Progenitor Cell Function Via Pulmonary Oxidative Stress - Haberzettl, Petra; Conklin, Daniel J.; Abplanalp, Wesley T.; Bhatnagar, Aruni; O’Toole, Timothy E. (Arteriosclerosis, thrombosis, and vascular biology, 2018)
Exposure to fine particulate matter (PM ) air pollution is associated with the depletion of circulating endothelial progenitor cells (EPCs), as well as vascular injury and dysfunction. Nevertheless, it remains unclear whether PM exposure leads to significant impairments in EPC function. Hence, we studied the effects of PM on EPC-mediated recovery of vascular perfusion after hindlimb ischemia and examined the mechanisms whereby PM exposure affects EPC abundance and function. In comparison with EPCs isolated from mice breathing filtered air, EPCs from mice exposed for 9 consecutive days (6 hours per day) to concentrated ambient PM (CAP) had defects in both proliferation and tube formation. However, CAP exposure of mice overexpressing extracellular superoxide dismutase (ecSOD-Tg) in the lungs did not affect EPC tube formation. Exposure to CAP also suppressed circulating EPC levels, VEGF (vascular endothelial growth factor)-stimulated aortic Akt phosphorylation, and plasma NO levels in wild-type but not in ecSOD-Tg mice. EPCs from CAP-exposed wild-type mice failed to augment basal recovery of hindlimb perfusion when injected into unexposed mice subjected to hindlimb ischemia; however, these deficits in recovery of hindlimb perfusion were absent when using EPCs derived from CAP-exposed ecSOD-Tg mice. The improved reparative function of EPCs from CAP-exposed ecSOD-Tg mice was also reflected by greater expression of and when compared with EPCs from CAP-exposed wild-type mice. Exposure to PM impairs EPC abundance and function and prevents EPC-mediated vascular recovery after hindlimb ischemia. This defect is attributed, in part, to pulmonary oxidative stress and was associated with vascular VEGF resistance and a decrement in NO bioavailability.